2016
DOI: 10.1200/jco.2015.63.4154
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase III Study Comparing Gefitinib With Erlotinib in Patients With Previously Treated Advanced Lung Adenocarcinoma: WJOG 5108L

Abstract: The study did not demonstrate noninferiority of gefitinib compared with erlotinib in terms of PFS in patients with lung adenocarcinoma according to the predefined criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
115
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 16 publications
3
115
4
1
Order By: Relevance
“…Zhang et al also showed that the patients with the exon 19 deletion in EGFR receiving first-line EGFR-TKIs had longer PFS than those with exon 21 substitution (16). Similarly, Urata et al identified patients with the EGFR exon 19 deletion subgroup had slightly longer PFS when treated with gefitinib and erlotinib than those with p.Leu858Arg mutation (14). Furthermore, analysis of two phase III trials, LUX-Lung 3 and LUX-Lung 6, indicated that the first-line afatinib compared to chemotherapy improved OS for patients with the EGFR exon 19 deletion but not for patients with p.Leu858Arg substitution (17).…”
Section: Univariate Analysis Multivariate Analysis Median Pfs -------mentioning
confidence: 94%
See 2 more Smart Citations
“…Zhang et al also showed that the patients with the exon 19 deletion in EGFR receiving first-line EGFR-TKIs had longer PFS than those with exon 21 substitution (16). Similarly, Urata et al identified patients with the EGFR exon 19 deletion subgroup had slightly longer PFS when treated with gefitinib and erlotinib than those with p.Leu858Arg mutation (14). Furthermore, analysis of two phase III trials, LUX-Lung 3 and LUX-Lung 6, indicated that the first-line afatinib compared to chemotherapy improved OS for patients with the EGFR exon 19 deletion but not for patients with p.Leu858Arg substitution (17).…”
Section: Univariate Analysis Multivariate Analysis Median Pfs -------mentioning
confidence: 94%
“…The authors concluded that the reason for treatment failure was including patients with unknown EGFR gene mutations with at least two out of three clinical factors associated with a higher incidence of EGFR gene mutations (6). Similarly, in a recent randomized phase III study of 562 pretreated patients with lung adenocarcinoma (including 401 with EGFR mutations), the response rates were 44 and 46% and the median PFS was 7.5 and 6.5 months in erlotinib-and gefitinib-treatment arms, respectively (14). The first head-to-head comparison of afatinib and gefitinib was recently reported in the prospective phase IIb LUX-Lung 7 clinical trial (7).…”
Section: Univariate Analysis Multivariate Analysis Median Pfs -------mentioning
confidence: 97%
See 1 more Smart Citation
“…In the randomized phase III trial of Urata and colleagues comparing gefitinib and erlotinib in previously treated adenocarcinoma, the number of patients who discontinued treatment due to toxicity was similar (33 and 32 patients, respectively) [Urata et al 2016]. As reported in previous trials, grade 3-4 rash toxicities were more frequent for erlotinib (18.1%) than for gefitinib (2.2%), whilst ALT/AST elevation was more common for gefitinib (6.2/13% for gefitinib versus 2.2/3.3% for erlotinib).…”
Section: Is There Evidence Of Different Efficacy Between Egfr Tkis Fomentioning
confidence: 96%
“…There have been two studies conducted in Asian patients which directly compared erlotinib and gefitinib, but were based on previously treated patients [Yang et al 2015c;Urata et al 2016]. Neither of these studies showed differences in PFS and OS between TKIs.…”
Section: Is There Evidence Of Different Efficacy Between Egfr Tkis Fomentioning
confidence: 99%